Internacionalização na Universidade Federal de Mato Grosso estudo de caso do Programa da Rede Amazônica de Educação em Ciências e Matemática - Simm, Ana Sophia Haagsma (2019)
The present research has as its general purpose to analyze the internationalization movement of the postgraduate program of the Amazon Network of Education in Mathematics and Sciences - PPGCEM / REAMEC. The choice of the REAMEC program was due to the fact that it is a network program consisting of three institutional poles (the Federal University of Mato Grosso – UFMT, the Federal University of Pará – UFPA and Amazonas State University – UEA) of the Legal Amazon Region, where, in theory, the possibilities of expanding partnerships are strengthed. The theoretical framework used to support the research comprises authors such as Knight (2004), Morosini (2006), De Wit (2010), Stallivieri (2004), whose works address the central theme of this research that is the internationalization of the postgraduation studies. The qualitative methodological approach based on the literature of Bogdan and Biklen (1994) was employed. The research is a case study and elements elaborated by Yin (2015) were used, considering the PPGCEM/REAMEC postgraduate program as the object of study. The data was produced in two stages, the first one was the survey, made at the Lattes-CNPq platform, of the international production, researches and international networks participation, and academic mobility of the REAMEC program graduates from the first and second groups, in their respective curricula. The second stage was the analysis of the speeches of the subjects in the context of the internationalization concerning the conception, identification of international activities and the challenges of the REAMEC doctoral program regarding the internationalization in postgraduate studies. The first stage data was analyzed through frequency and percentage and the data of the second stage through content analysis. Concerning the Lattes curriculum of the graduates, there are initiatives regarding the strategies and international publications. Regarding the academic-scientific productions, a great number of publications in journals with international index was verified, when compared with the international journals. This is justified due to the large number of Brazilian journals that have index. When analyzing the speeches of the subjects, this research shows a timid presence of the internationalization in the activities of the program. But the international publications framework (in its beginning) and the motivation among the managers, accredited teachers and graduates was identified. In order to strengthen the international scope of the program, it is necessary to work in the articulation between the program and the academic centers, as well as all the IES accredited to the program. In designing this goal and working on its articulation, the doctoral program in network, REAMEC, can enhance its internationalization and help in the elaboration and re-elaboration of institutional policies, regarding the internationalization of postgraduate programs, in the universities of the Amazon region.